Understanding of the electrochemical behaviors of aqueous zinc–manganese batteries: Reaction processes and failure mechanisms - Luo, Xinyu; Peng, Wenchao; Li, Yang; Zhang, Fengbao; Fan, Xiaobin (Green energy & environment, 2022)
As one of the most common cathode materials for aqueous zinc-ion batteries (AZIBs), manganese oxides have the advantages of abundant reserves, low cost, and low toxicity. However, the electrochemical mechanism at the cathode of aqueous zinc–manganese batteries (AZMBs) is complicated due to different electrode materials, electrolytes and working conditions. These complicated mechanisms severely limit the research progress of AZMBs system and the design of cells with better performance. Hence, the mechanism of AZMBs currently recognized by most researchers according to the classification of the main ions involved in the faradaic reaction is introduced in the review. Then a series of reasons that affect the electrochemical behavior of the battery are summarized. Finally, the failure mechanisms of AZMBs over prolonged cycling are discussed, and the current insufficient research areas of the system are explained, along with the direction of further research being prospected.